Evolution of beverage portion sizes consumed in Brazil between 2008 and 2018 - Cavalcante, Jessica Brito; Vasconcelos, Thais Meirelles de; Sichieri, Rosely; Bezerra, Ilana Nogueira (Frontiers in Public Health, 2023)
Objective To describe the evolution of beverage portion sizes consumed in Brazil between 2008 and 2018. Methods Data from the dietary surveys of 2008–2009 and 2017–2018 Brazilian Household Budget Surveys, conducted with 34,003 and 46,164 individuals, respectively, were used to analyze the portion size of beverages. Food consumption data were used to group beverages according to nutritional characteristics, type and size of portions into eight groups: high-calorie soft drinks, fruit refreshments, alcoholic beverages, coffee/tea, fruit juices, milk and milk substitutes and ultra-processed milk-based beverages. The two-day food record and recall were considered to analyze the consumed portions. Comparisons between the surveys were done using Chi-Square tests and linear regression models. Results Between 2008 and 2018, the average portion consumed showed a significant increase for the group of alcoholic beverages (+29%), flavored juices (+11%), caloric soft drinks (+8%), milk and milk substitutes (+6%) and fruit juices (+5%); and reduction for the coffee/tea group (−11%). Analyzes by age group showed that among individuals between 20 and 40 years of age, the soft drinks and alcoholic beverage groups showed the greatest increase in portion size, +12 and +44%, respectively. Conclusion The beverage portion sizes consumed in Brazil between 2008 and 2018 increased for the group of alcoholic beverages, flavored juices, caloric soft drinks, milk and milk substitutes, and fruit juices.